Impact of Anxiety on Quality of Life in Parkinson's Disease - Kristine K. Hanna; Alice Cronin-Golomb (Parkinson's Disease)
In Parkinson's disease (PD), both the patient and the health care provider look for ways to preserve the patient's quality of life. Many studies focus on the impact of depression and motor disability on poor life quality but neglect to examine the role of anxiety. We investigated the impact of anxiety and depression on health-related quality of life in PD, using the Parkinson's Disease Quality of Life measure (PDQ-39). Symptoms of anxiety, more than depression, cognitive status, or motor stage, significantly affected quality of life in 38 nondemented patients with mild-to-moderate motor disability. Stepwise regression analyses revealed that anxiety explained 29% of the variance in the PDQ-39 sum score, and depression explained 10% of the variance beyond that accounted for by anxiety. The findings suggest that primary management of anxiety as well as depression may be important to optimizing the quality of life of PD patients.